Analysis of the Internal and External Environment of the North Kalimantan Regional Police Organization in Maintaining the Security of the RI-Malaysia Border Area - Kwarta, Helmi; Rahayu, Rahayu; Warsono, Hardi; Dwimawanti, Ida Hayu (Budapest International Research and Critics University, 2022)
An organization is a consciously coordinated social entity, with a relatively identifiable boundary, that works on a relatively continuous basis to achieve a common goal or set of goals (Stephen & Judge, 2015). This study aims to analyze the internal and external environment of the North Kalimantan regional police organization in maintaining security in the RI-Malaysia border area. By using qualitative research methods. The results of the study indicate that currently the supporting factors in the North Kalimantan regional police organization are organizational structure and organizational culture. Meanwhile, those outside the North Kalimantan regional police organization are community groups and companies. This is due to the orderliness of border communities in guarding the RI-Malaysia border area as evidenced by the decrease in crime in 2020-2021. In 2020 the number of crimes reached 1,079 cases and decreased in 2021 to 890 cases of crime. And all groups of companies participated by providing CSR funds to build the current Kaltara Polda. The inhibiting factor can be seen that currently the resources owned by the North Kalimantan regional police organization are still limited, starting from the absence of a budget, the number of member personnel who secure border areas, and the PLBN infrastructure facilities whose construction has not yet been completed due to the COVID-19 pandemic in the RI-Malaysia border area in North Kalimantan Province.